Genotoxicity of Copper and Nickel Nanoparticles in Somatic Cells of Drosophila melanogaster. (19th July 2018) - Carmona, Erico R.; García-Rodríguez, Alba; Marcos, Ricard
Abstract : Copper and nickel nanoparticles (Cu-NPs and Ni-NPs, respectively) are used in a variety of industrial applications, such as semiconductors, catalysts, sensors, and antimicrobial agents. Although studies on its potential genotoxicity already exist, few of them report in vivo data. In the present study we have used the wing-spot assay in Drosophila melanogaster to determine the genotoxic activity of Cu-NPs and Ni-NPs, and these data have been compared with those obtained with their microparticle forms (MPs). Additionally, a complete physical characterization of NPs using transmission electronic microscopy (TEM), dynamic light scattering (DLS), and laser Doppler velocimetry (LDV) techniques was also performed. Results obtained with Cu-NPs and Cu-MPs indicate that both failed to induce an increase in the frequency of mutant spots formation in the wings of the adults, suggesting a lack of genotoxicity in somatic cells of D. melanogaster . However, when Ni-NPs and Ni-MPs were evaluated, a significant increase of small single spots and total mutant spots was observed only for Ni-NPs (P<0.05) at the highest dose assessed. Thus, the genotoxicity of Ni-NPs seem to be related to their nanoscale size, because no genotoxic effects have been reported with their microparticles and ions. This study is the first assessing the in vivo genotoxic potential of Cu-NPs and Ni-NPs in the Drosophila model.